Enhancing sound transmission loss of polyurethane foams using waste soda glass filler - Yesilyurt, Aysenur (My University, 2024)
Sound transmission mechanisms and sound transmission losses are of great importance in providing acoustic comfort. Research has focused on developing materials and structures that will reduce sound transmission loss. The increasing amount of waste disrupts the ecological balance; this situation brings about global warming, air and soil pollution. These environmental effects negatively affect the lives of all living things, especially humans, and also harm the economy. Combating global pollution has become one of the primary goals of scientists. Recycling provides significant economic benefits as well as protecting both human health and natural resources. In this study, polyurethane foams used in the automotive industry and many other areas were produced by adding waste soda glass powder at various rates while keeping the isocyanate/polyol ratio constant. The durability of the produced foams was tested by apparent density measurement, wettability by contact angle analysis, organic bond structures by FT-IR spectroscopy and acoustic properties by sound transmission loss analysis. It was determined that soda glass powder did not react with the foams and that the produced foams exhibited hydrophobic properties. The acoustic properties of the filler foams were higher than the neat foam in almost the entire frequency range (65-6300 Hz). The sample coded PU-SG4 is the sample that exhibits the best acoustic properties by reaching 9.28 dB, 9.10 dB and 13.48 dB values in the low, medium and high frequency regions, respectively. In the high frequency range region, all of the soda glass added foam composites reached a sound transmission loss of over 13 dB.
Keywords: Sound transmission loss; Polyurethane foam; Waste soda glass